Enhancing delay differentiation semantics of class-based IP networks - Sousa, Pedro (2004)
This paper presents a time-sensitive scheduler oriented to delay differentiation in class-based networks, studying its behaviour from a single node to an end-to-end perspective. The novel feature of this scheduler is that it tries to bound the queuing delay per class and, simultaneously, to control the excess queuing delays in order to avoid class starvation. The study analyses the scheduler behaviour for heterogeneous class-load distributions and distinct timescales proving the robustness of the mechanism. Discussion on its operational feasibility conditions is carried out and configuration guidelines for its use are provided. In addition, the paper proposes a new queue selection procedure in order to improve its performance in high speed networks.